A Functional Investigation of the Conjunction aunque in Spoken Iberian Spanish - Gasparini Bastos, Sandra Denise [UNESP]; Garcia Parra, Beatriz Goaveia [UNESP] (Univ Federal Minas Gerais, Fac Letras, 2015)
This paper aims at describing the elements that characterize the concessive clauses introduced by aunque in spoken Iberian Spanish. The analysis was based on the layered structure of the clause proposed by Hengeveld (1988, 1989) and Dik (1989), from a functional perspective of language, and on the adaptation of this model for concessive clauses (CREVELS, 1998, 2000a, 2000b). Results showed that the conjunction aunque may function in different layers, introducing structures that can only be described beyond the limits of the clause.
Keywords: Concessive clauses; Conjunction aunque; Functional Grammar; Spoken Iberian Spanish